Significance of serum protein electrophoresis in diagnosing multiple myeloma: A retrospective study at a tertiary care centre - Shrinidhi Sundar; Swetha Raghavendra Prasad; Dhivya Senthil Kumar; Sathya Selvarajan; Sowmya Krishnamurthy; Sridharan Kopula Sathyamurthy (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
Multiple myeloma (MM) is a hematologic malignancy characterized by uncontrolled plasma cell proliferation in the bone marrow, initially asymptomatic, often causing symptoms like bone pain, anemia, renal dysfunction, and increased infection susceptibility. The study investigates the clinical significance of inconsistencies in albumin measurement methods in multiple myeloma patients, focusing on serum protein electrophoresis (SPEP) and the bromocresol green (BCG) assay. A comparative analysis was conducted to evaluate the differences between albumin levels measured by SPEP and BCG, exploring how these variations relate to disease severity and treatment decisions in MM patients. According to the results, SPEP albumin levels were significantly higher than BCG albumin levels in MM patients (p <0.001). This difference is clinically significant, as lower BCG albumin readings could overestimate disease severity, potentially leading to misclassification and affecting treatment decisions. Accurate albumin measurement is crucial for proper staging and prognosis in multiple myeloma. In conclusion, this highlights the need to integrate SPEP and biochemical markers for more precise diagnosis and timely intervention. While SPEP is essential for diagnosing MM and monitoring M-protein (also known as monoclonal immunoglobulin or paraprotein), the BCG method remains useful for staging and prognosis. Standardizing laboratory protocols and exploring novel biomarkers could improve MM diagnosis, ensuring more accurate disease classification and better patient management. Further research is needed to assess the long-term impact of these discrepancies on treatment outcomes and survival rates.